Simulation to clarify the effect of paddling motion on the hull behavior of a single kayak in a sprint race - Nakashima, M.; Kitazawa, A.; Nakagaki, K.; Onoto, N. (Sports Engineering, 2017)
The cause and effect relationship between the paddling motion and the hull behavior of a kayak in a sprint race has not been sufficiently investigated. The objective of this study was to investigate the effect of the paddling motion on the hull behavior by numerical simulation. A dynamic simulation model of a paddler, paddle and hull in a single kayak, which was previously developed, was used for the simulation. One standard paddling motion and three modified motions were prepared for the simulation. Three modified motions were created based on suggestions by coaches of the Japan Olympic team. These motions were thought to be often seen in paddlers of lower skill level and, therefore, empirically considered to be typically bad motions. From the simulation results, the following findings were obtained: in the simulation of the standard paddling motion, the averaged hull velocity was 5.4 m/s. This was consistent with the actual hull velocity of 5.5 m/s. Typically bad motions which induced undesirable hull fluctuations reduced the propulsive efficiency.